This is your life, Harriet Chance! : a novel - Evison, Jonathan (Algonquin Books of Chapel Hill, 2015)
Embarking on an ill-conceived Alaskan cruise, septuagenarian Harriet reunites with her estranged daughter and confronts pivotal events from her life surrounding the true character of her husband, who died two years earlier.